2013
DOI: 10.1103/physreve.88.052116
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the dispersion transition and nonergodicity of a system consisting of a disordered porous medium and a nonwetting liquid

Abstract: An approach has been proposed for the description of the dispersion transition of a nonwetting liquid in confinement. This approach describes intrusion and extrusion processes for the ground state of a disordered porous medium, which is characterized by the formation of a fractal percolation cluster. The observed transition of the system of liquid nanoclusters in confinement to a metastable state in a narrow range of degrees of filling and temperatures has been explained by the appearance of a potential barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…In references [6,7], it was shown that at the intrusion and extrusion of liquids, the consideration of such non-uniform geometric configurations can be done by the functions W and W 1 , respectively. In the case of extrusion, the quantity W ðz; θ 1 Þ takes into account the interaction liquid clusters in neighbouring pores and is determined as the difference between the average number of menisci before and after the depletion of the pore per nearest neighbour.…”
Section: Physics and Chemistry Of Liquidsmentioning
confidence: 99%
See 4 more Smart Citations
“…In references [6,7], it was shown that at the intrusion and extrusion of liquids, the consideration of such non-uniform geometric configurations can be done by the functions W and W 1 , respectively. In the case of extrusion, the quantity W ðz; θ 1 Þ takes into account the interaction liquid clusters in neighbouring pores and is determined as the difference between the average number of menisci before and after the depletion of the pore per nearest neighbour.…”
Section: Physics and Chemistry Of Liquidsmentioning
confidence: 99%
“…According to the authors in References [6,7] and considering a narrow pore size distribution of the porous medium, it can be assumed that the function W 1 depends only on the degree of filling, and the number of nearest neighbours can be taken constant, then with this in mind, the sum in Equation (1) can be calculated analytically:…”
Section: Physics and Chemistry Of Liquidsmentioning
confidence: 99%
See 3 more Smart Citations